Pengaruh aktivitas ukm ukor terhadap minat dan bakat mahasiwa UIN Sunan Ampel Surabaya - Rosyidah, Ainur; Ramadhanty, Anjani Suci; Sausan, Zuhriah; Falasifah, Nihlatul; Jamaluddin, Ahmad Sulthon (Universitas Hamzanwadi, 2023)
This study aims to determine the effect of ukm ukor activities on the talent interests of UIN Sunan Ampel Surabaya students. This research is a quantitative research with data collection methods carried out through questionnaires using the Google form. The research subjects were 30 students. Data processing is done using SPSS software. The instrument analysis performed was validity and reliability. While the data analysis technique used is the normality test and hypothesis testing which consists of multiple linear regression analysis, F test (simultaneous), test the coefficient of determination (R2), and t test (partial). Based on the normality test, it can be seen if the data is normal because p > 0.05, which is equal to 0.2. The F test (simultaneous) is obtained if Fcount > Ftable, namely the value of 19.331 > 1.955 which indicates that Ha is accepted, which means there is an influence. The conclusion in the study is that there is an influence of ukm ukor activities on the interests and talents of UIN Sunan Ampel Surabaya students, namely based on the F test (Stimulant) that students, ukm, sports, and participation greatly influence interests and talents.